ISMS Evaluation Using KAMI Index v.4 Based on ISO/IEC 27001:2013 (Case Study: Koperasi XYZ) - I Putu Noven Hartawan (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2021)
Koperasi is one of the main pillars in supporting the Indonesian economy. Koperasi is based on the principle of kinship. Capital from the koperasi business is obtained from all its members. Koperasi XYZ has 1341 members. The koperasi XYZ savings and loan unit uses an information system to manage data. The application of this information provides a gap in the security of member information. In order to maintain the trust of members, the koperasi XYZ must take steps to secure the information held. Information Security Management System (ISMS) is a policy that can be taken to solve information security problems. ISO / IEC 27001 is an international standard in the application of ISMS. The Ministry of Communication and Informatics released the KAMI index evaluation alt which is SNI ISO / IEC 27001. The ISMS audit on the koperasi XYZ shows that the importance of electronic systems in the koperasi XYZ is included in the high category. And the US index results show that the koperasi XYZ is not yet feasible / meets ISO / IEC 27001: 2013 standards